The C-terminal region of Trypanosoma cruzi MASPs is antigenic and secreted via exovesicles - de Pablos, Luis Miguel (2016)
Trypanosoma cruzi is the etiological agent of Chagas disease, a neglected and emerging tropical disease, endemic to South America and present in non-endemic regions due to human migration. The MASP multigene family is specific to T. cruzi, accounting for 6% of the parasite´s genome and plays a key role in immune evasion. A common feature of MASPs is the presence of two conserved regions: an N-terminal region codifying for signal peptide and a C-terminal (C-term) region, which potentially acts as GPI-addition signal peptide. Our aim was the analysis of the presence of an immune response against the MASP C-term region. We found that this region is highly conserved, released via exovesicles (EVs) and has an associated immune response as revealed by epitope affinity mapping, IFA and inhibition of the complement lysis assays. We also demonstrate the presence of a fast IgM response in Balb/c mice infected with T. cruzi. Our results reveal the presence of non-canonical secreted peptides in EVs, which can subsequently be exposed to the immune system with a potential role in evading immune system targets in the parasite.